ANALISIS FAKTOR GESEKAN PADA PIPA LURUS DENGAN VARIASI DEBIT ALIRAN - Subagyo, Rachmat (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
Distribution of laminar or turbulent flow is strongly influenced by the Reynolds number, Viscosity, pressure gradient and surface roughness. High coefficient of friction affect directly to a substantial reduction in pressure and eventually to the energy needed to push the fluid. Because of the role of the coefficient of friction is very important in the flow, so study has been conducted on the straight pipe, and friction factor with the variation of flow rate, by measuring pressure at two particular points to determine the loss. From the experimental results it can be concluded that the friction factor will be smaller in value with increasing Reynolds number and with the increase of Re, the friction factor value will be more stable. In the first experiment the highest friction factor occurs at Re = 4,30 x 104 with a value of f = 2,195 x 10-2 for the second experiment at Re = 1,41 x 104 with a value of f = 2,462 x 10-2 and the third experiment at Re = 2,39 x 104 with a value of f = 2,461 x 10-2. And for the lowest value occurred at Re = 1,91 x 105 with a value of f = 1,513 x 10-2, Re = 1,86 x 105 with a value of f = 1,521 x 10-2 and Re = 1,75 x 105 with a value of f = 1,544 x 10-2. At Re numbers began to 1,50 x 104 - 2 x 104 value of the friction factor tends to be stable (unchanged). The difference calculation from the experimental to the theoretical friction factor is 1,37% and to the moody diagram is = 1,14%.